STUDI BHAKTI ADVAITA VEDANTA ADI SHANKARACHARYA DAN VAISNAVAISME - Suryanata, I Putu Gede (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Philosophy teach us how to be intelligence and criticism and refutes what is right. But from this we must cultivate the virtuous nature of religion. The cause of God shows themselves. Therefore philosophy must include the spirit of devotional service in Hinduism and even form a branch of Bhakti-Vedanta philosophy. Vedanta philosophy is divided into sub-systems namely Bhedabheda, Advaita, Dvaita, neo Vedanta. Vedanta figures such as Sankaracharya, Ramanujacharya, Madhavacharya, Nimbarka, Vallaba, Caintanya are philosophers of Vedanta. However, an important difference in his views on atman, soul, brahman and the world and their respective relationships in accordance with their development, Vedanta developed in a sub-system known as Bhakti-Vedanta, Visistadvaita, Dvaitadvaita, Dvaita, Suddhadvaita, Acintya Bhedabheda. established religion better known as Vaisnava Dharma.